Assessment of Provincial Air Quality based on Air Quality Index during 2016~2022 대기환경지수 기반 2016~2022년 시도별 대기오염물질의 농도 변화 분석 - Park, Junheung; Kim, Eunhye; Kang, Yoon Hee; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2024)
In this study, we analyzed changes in criteria air pollutant concentrations across provinces using data from the urban air quality monitoring network spanning 2016 to 2022. We also examined shifts in the Air Quality Index (AQI) from a health impact perspective. Over the seven-year period, national average concentrations of SO2, NO2, CO, PM2.5, and PM10 decreased by 41.1% (1.9 ppb), 27.4% (6.2 ppb), 19.4% (96.6 ppb), 32.9% (8.6 µg/m3 ), and 32.8% (15.4 µg/m3), respectively. However, O3 concentration increased by 6.4% (3.1 ppb). After excluding the impacts of foreign emissions, the impacts of domestic emissions resulted in concentration decreases of 24.8% for SO2 and increases of 5.1% for CO. O3 concentrations rose in most provinces, particularly in cities with high NOx emissions, suggesting reduced NO titration due to lowered NOx emissions. From the AQI perspective, the most significant air quality improvement during the study was for PM2.5, followed by PM10 and NO2. In general, PM2.5 showed the highest daily AQI in winter and O3 in summer during 2016~2018. However, with worsening O3 in 2020~2022, O3 determined the highest AQI on more days. Notably, O3 increase was pronounced in densely populated areas like the Seoul Metropolitan Area, warranting further research on health impact changes, including the population-weighted concentrations. Based on AQI assessments, PM2.5 and O3 require urgent reduction efforts. Considering the nature of secondary air pollutants, future air quality management in South Korea should prioritize gaining scientific understanding of their source-receptor relationship to develop cost effective control strategies, alongside precursor emission controls.
Keywords: 2016~2022; Air Quality Index; Concentration; Criteria air pollutants; South Korea